Tritopic NHC Precursors: Unusual Nickel Reactivity and Ethylene Insertion into a C(sp3)–H Bond. Issue 41 (31st August 2017) - Ren, Xiaoyu; Gourlaouen, Christophe; Wesolek, Marcel; Braunstein, Pierre
Abstract: The imidazolium chloride [C3 H3 N(C3 H6 NMe2 )NC(Me)(=NDipp)]Cl (1 ; Dipp=2, 6‐diisopropyl phenyl), a potential precursor to a tritopic N imine C NHC N amine pincer‐type ligand, reacted with [Ni(cod)2 ] to give the Ni I ‐Ni I complex 2, which contains a rare cod‐derived η 3 ‐allyl‐type bridging ligand. The implied intermediate formation of a nickel hydride through oxidative addition of the imidazolium C−H bond did not occur with the symmetrical imidazolium chloride [C3 H3 N2 C(Me)(=NDipp)2 ]Cl (3 ). Instead, a Ni−C(sp 3 ) bond was formed, leading to the neutral N imine CHN imine pincer‐type complex Ni[C3 H3 N2 C(Me)(=NDipp)2 ]Cl (4 ). Theoretical studies showed that this highly unusual feature in nickel NHC chemistry is due to steric constraints induced by the N substituents, which prevent Ni−H bond formation. Remarkably, ethylene inserted into the C(sp 3 )−H bond of 4 without nickel hydride formation, thus suggesting new pathways for the alkylation of non‐activated C−H bonds. Abstract : Pincers select ! Reaction of [C3 H3 N2 C(Me)(=NDipp)2 ]Cl with Ni 0 yielded the N imine CHN imine complex 4, which contains a Ni−C(sp 3 ) bond. Calculations showed that the unusual lack of oxidative addition of the imidazolium C(sp 2 )−H bond is due to geometrical constraints resulting from the pincer structure. Remarkably, ethylene inserted into the non‐activated N2 C(sp 3 )−H bond of 4 .